ASSESSMENT OF PSYCHOLOGICAL RESPONSES AND RELATED FACTORS OF DISCHARGED PATIENTS WHO HAVE BEEN HOSPITALIZED WITH COVID-19 - Cansel, Neslihan; Tetik, Burcu Kayhan; Demi, Gulsu Hilal; Kurt, Osman; Evren, Bahri; Yucel, Aytac (Medicinska Naklada, 2021)
Background: COVID-19 is the biggest pandemic of the last century. While a large number of cases and mortality rates direct the research to the clinic and prognosis of the disease, the mental health of these patients has recently become a matter of concern. This study aims to predict psychiatric morbidity and possible associated markers in COVID-19 survivors. Subjects and methods: A total of 102 survivors with COVID-19 infection participated in this study. A questionnaire was applied to the participants to evaluate demographic variables, history of comorbid diseases, smoking, loss of a relative due to COVID-19, and environmental attitudes after the discharge. Length of hospitalization, lung findings, intensive care history and treatments were recorded. Psychiatric morbidities were evaluated with General Anxiety Disorder-7, Patient Health Questionnaire-9 and The Results: Anxiety was found in 20.6%, depression in 13.7% based on moderate and above levels, 21.6% had significant PTSD. Female gender, history of psychiatric and comorbid diseases, smoking, perceived discrimination, and lack of long-lasting immunity posed a risk in terms of psychological response. There was a negative correlation between age and depression scores. No relation was found between the duration of hospitalization, presence of lung involvement, receiving intensive care treatment, losing a relative due to COVID-19 and psychological response. Conclusions: On patients treated for COVID-19 infection, psychological response continue after discharge. Mental health support and efforts to reduce stigma among infected subjects can reduce the psychological impact caused by the pandemic.
Keywords: COVID-19; survivors; anxiety; depression; post-traumatic stress